Numerical Simulation of Wave Run-Up on Coastal Structure with Hexaloc Armour Units based on the SPH Method - Ghazali Hafiz, Muhammad Brilliant Danu; Armono, Haryo Dwito; Zikra, Muhammad (Department of Naval Architecture - Diponegoro University, 2026)
Coastal abrasion and erosion pose a threat to shoreline stability in Indonesia, necessitating the implementation of reliable coastal protection structures, such as breakwaters. Accurate prediction of wave run-up is essential, as crest elevation is crucial, as it directly determines structural safety and the level of protection provided. This study aims to analyse wave run-up on rubble-mound breakwaters with Hexaloc armour units using the Smoothed Particle Hydrodynamics (SPH) method in DualSPHysics, to improve the accuracy and efficiency of design. The numerical model was developed using AutoCAD, SketchUp and simulated under varying wave heights (0.05 – 0.13 m), periods (1.1 – 1.5 s), and one versus two layer armour configurations. Validation was carried out by comparing simulation results with analytical and empirical formulations, particularly Ahrens’ equation. The results indicate that relative run-up ( ) increases with the Iribarren number but tends to stabilize at higher values. Numerical simulations produced run-up ratios ranging from 0.56 – 1.66 for a single layer and 0.63 – 0.86 for a double layer, while theoretical predictions yielded higher values of 1.59 – 2.39. The comparison demonstrates that single-layer Hexaloc arrangements produced slightly higher run-up than double layers, due to increased permeability. A strong correlation was obtained between SPH results and Ahrens’s theory, with a coefficient of determination of for a single layer, for a double layer, confirming that both approaches yield consistent outcomes.